Addressing international mobility confusion - developing definitions and differentiations for self-initiated and assigned expatriates as well as migrants - Andresen, Maike; Bergdolt, Franziska; Margenfeld, Jil; Dickmann, Michael (Taylor & Francis, 2014)
The literature on international human resource management indicates a growing array of different forms of international work experiences such as assigned and self-initiated expatriation. However, the criteria for demarcation of these different forms and the term ‘migrant' are often unclear which leads to an unfortunate lack of comparability of research and a potential confusion for readers. Based on the sociological, psychological and economics literature, this article reviews and synthesizes the existing definitions of the three terms in the current research. A qualitative content analysis and the Rubicon model [Heckhausen, H., and Gollwitzer, P.M. (1987), ‘Thought Contents and Cognitive Functioning in Motivational Versus Volitional States of Mind', Motivation and Emotion, 1, 101-120.] are used as a theoretical base to structure the findings. The paper creates a criteria-based definition and differentiation of terms and then develops a typology of four different types of expatriates: assigned expatriates, interself- initiated expatriates, intra-self-initiated expatriates and drawn expatriates. Implications for management as well as for future research are outlined.
Keywords: assigned expatriate; drawn expatriate; expatriate typology; qualitative content analysis; migrant; self-initiated expatriate